A bibliometric analysis of the presence of finances in high-impact tourism journals. Issue 3 (17th February 2017) - Jiménez-Caballero, José Luis; Polo Molina, Silvia
Abstract : The purpose of this study is to observe the presence of financial research applied to tourism during the 1995–2012 period. The Scopus database has been used for tourism journals indexed in Journal Citation Reports and the Mendeley reference manager was used to manage the results. Two hundred and fifty-two articles were selected with basically financial content. The results reveal that in the majority of cases empirical research typology was used; the subject matter that aroused most interest was corporate finances and, within this, financial management, value creation, capital structure and investment decisions .